The translation of figurative language in Kazi Nazrul Islam’s poems / Shafia Akhter - Akhter, Shafia (2014)
Translating poems are more challenging than translating academic texts. Translators usually face problems in translating figurative language as they have to make a balance between the target language (TL) and the source language (SL) in order to preserve the meaning when translating to the TL so that it is accepted socio-culturally by the TL readers. This study investigates the translation of figurative language (similes, metaphors, metonymy, synecdoche, allusions, personifications and hyperboles) in thirty selected Bengali poems by Kazi Nazrul Islam, the national poet of Bangladesh, from Bengali to English. The aims of this research are to investigate the types of figurative language used by the poet, to determine the strategies used by the translator in translating the figurative language, and to recommend better translation strategies for the figurative language that has not been translated appropriately in the TL. In conducting the study, the researcher has used an eclectic procedure as the theoretical framework of study comprising the translation strategies proposed by Newmark (1988) to translate similes and metaphors, Larson’s (1998) strategies to translate metonymy and synecdoche, Leppihelme’s (1997) strategies to translate allusions and Baker’s (2011) strategies to translate personifications and hyperboles. A total of 371 instances of figurative language were found in these thirty poems, where metaphors were the most frequently used i.e. 152 instances (40.97%). This was followed by personifications with a total of 62 instances (16.71%), allusions 58 instances (15.63%), metonymy 55 instances (14.82 %), similes 18 instances (4.85%), and hyperboles 14 instances (3.77%) and synecdoche 12 instances (3.23%). It was further revealed that several strategies suggested by Newmark, Larson, Baker and Leppihalme were applied and while translating, attempts were made to retain the same image in the target language. Another new strategy that was found was the strategy of omission in translating metonymy and synecdoche which was not mentioned by Larson. The findings from this study may offer good guidelines and insights for future translators in choosing suitable strategies for translating figurative language accurately in poems.